Improving Employee Work Motivation at PT.X through Stress Management Training: An Experimental Study on the Production Team - Konto Iskandar Dinata; Umi Nur Kholifah Dinata (Psycho Holistic, 2023)
This study aimed to determine the impact of stress management training on the work motivation of production employees at PT. X. The hypothesis of the study posited that the work motivation of employees would be higher after receiving stress management training compared to before the training. The study involved 11 production employees who exhibited low to moderate work motivation and experienced high to moderate job stress. The data collection technique employed in this study was the work motivation scale. The research design utilized a one-group pre-test post-test design, and the data were analyzed using the Wilcoxon signed-rank test, a non-parametric statistical analysis. The results of the Wilcoxon test revealed a significance value of 0.003 < 0.050, indicating that the research hypothesis was supported. Therefore, a significant difference in work motivation was observed between the pre-training and post-training phases among the employees.